The Relations Among the Three Motivational Theories in Tourism by Plog, Cohen and Pearce - Shahzalal, M. (Advances in Social Sciences Research Journal, 2022)
Tourist motivation is the center of all travel planning. Although many motivational theories evolved in tourism literature to explain tourist behavior, a few are used to develop tourists’ typologies. The tourists’ psychographic profile (Plog, 1974, 2001), travel career ladder (Pearce, 1988, 1993, 2005), and strangeness and familiarity (environmental bubble) framework (Cohen, 1972) theories are widely applied in empirical studies in this respect amongst other theories. This paper aims to describe these three theories individually and critically explain their interrelationships. This paper may facilitate academics and researchers to enrich their understandings of these three theories, tourists to understand their destination choice and motivations and the managers of tourism businesses to formulate policies to attract tourists with different motives.